2014
DOI: 10.1136/jfprhc-2013-100600
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of extended use of the combined oral contraceptive pill

Abstract: Background Extended use of the combined oral contraceptive pill (COC), defined as taking active pills for at least 28 days, has been used in order to avoid bleeding at important times and to treat gynaecological conditions such as endometriosis. We examined the main issues involved in extended use of the COC and how it has evolved from being one of medicine's best-kept secrets to becoming more widely accepted by women and the medical community. Study design Literature review, using Medline, Embase, Pubmed, CIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 91 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…It is well documented that some women prefer regularly scheduled bleeding and consider absence of scheduled bleeding highly undesirable, and counseling about possible absence of scheduled bleeding with particular regimens will be especially important for these women 11,32. The balance that each woman will need to consider with extended-regimen COC is the high satisfaction reported with reduced bleeding overall, improvement in menstrual cycle-related symptoms and disorders, and reduction in inconvenience and interference with daily activities vs the individual significance of potential unscheduled bleeding or spotting, particularly in the earliest cycles of treatment 4,5,12,24. High satisfaction and improved QOL may overcome the inconvenience of unscheduled bleeding or spotting, as shown among women with menstrual cycle-related symptoms who received extended-regimen COC and chose to continue the regimen, even with persistent breakthrough bleeding or spotting episodes 33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that some women prefer regularly scheduled bleeding and consider absence of scheduled bleeding highly undesirable, and counseling about possible absence of scheduled bleeding with particular regimens will be especially important for these women 11,32. The balance that each woman will need to consider with extended-regimen COC is the high satisfaction reported with reduced bleeding overall, improvement in menstrual cycle-related symptoms and disorders, and reduction in inconvenience and interference with daily activities vs the individual significance of potential unscheduled bleeding or spotting, particularly in the earliest cycles of treatment 4,5,12,24. High satisfaction and improved QOL may overcome the inconvenience of unscheduled bleeding or spotting, as shown among women with menstrual cycle-related symptoms who received extended-regimen COC and chose to continue the regimen, even with persistent breakthrough bleeding or spotting episodes 33…”
Section: Discussionmentioning
confidence: 99%
“…Monthly cyclic regimens, including 21/7 or 24/4 regimens, remain the most common; however, use of extended-regimen COC is increasing 3. COC extended regimens include greater than 28 days of active pills, reduce the number of scheduled bleeding episodes, and may maintain, modify, or eliminate the usual 7-day hormone-free interval (HFI) that occurs within the traditional 28-day regimen 4. The utility of extended-regimen COC for women may include improvement in medical conditions, such as premenstrual syndrome (PMS), dysmenorrhea, menstrually-related headaches, endometriosis, iron deficiency, and anemia, as well as reduced inconvenience and interference with daily activities, work/school attendance, personal social events, and sports; overall improved quality of life (QOL); and economic benefits related to reduced expenses for feminine products and reduced use of pain medication 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…Histological examinations of the endometrial lining have, however, confirmed an inactive endometrium, likely induced from adequate progestin exposure, in women using either cyclical or extended regimens 16 , 74 . These findings have been confirmed by multiple large trials of extended regimen COCs, demonstrating that long-term use of these regimens does not cause endometrial pathology but largely produces an atrophic endometrium 42 , 46 , 74 . Similarly, an analysis of the endometrial effects of an extended LNG 150 μg/EE 30 μg + EE 10 μg COC found no evidence of endometrial hyperplasia and confirmed the endometrial safety of this regimen 75 .…”
Section: Resultsmentioning
confidence: 68%
“…Although most studies report an increased incidence of unscheduled bleeding with extended regimens during early cycles 16 , 42 , it has also been consistently documented that the frequency and intensity of such bleeding decreases over time 42 . By the fourth extended cycle, the incidence of unscheduled bleeding is generally comparable to that seen among users of conventional cyclical regimens 34 , 46 .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation